Partisipasi Anggaran, Prestasi Manajer Dan Pengaruh Komitmen Organisasi Sebagai Variabel Intervening Terhadap Kinerja Perusahaan Manufaktur Di Indonesia - Margareta Diana Pangastuti (Ekopem: Jurnal Ekonomi Pembangunan, 2019)
Budgetary participation, manager achievement, the influence of organizational comitment at performance manufacturing bisnis in Indonesia. Some previous studies stated that he relationship between budgetary participation and managers’ performance was positive and significant, and the others confirmed otherwise. Inserting intervening or moderating variables in that relationship, could solve the difference. This research analyzes the influence of participation budget arrangement on the managers’ performance, in which the organizational commitment at Performance Manufacturing Bisnis is treated as the intervening variable. There in the direct, positive, and significant influence of the participation on the managers performance. The more intense the budgetary participation, the higher his/her work performance will be. Moreover, when the organizational commitment and performance are the intervening variables, the recent influence of the participation on he manager’s performance become weaker. This indicates that the strength of that influence is indirect, through the organizational commitment at Performance Manufacturing Bisnis.